PENGARUH KEMAMPUAN BERPIKIR KRITIS DAN PENGUASAAN KOSAKATA TERHADAP KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA (SURVEI PADA MA SWASTA DI KABUPATEN SERANG) - Yusuf Hekmatiar (INFERENCE: Journal of English Language Teaching, 2019)
The purpose of this study was to determine the effect of critical thinking skills and vocabulary mastery of English Madrasah Aliyah private speaking skills in Serang District. The research method used to analyze critical thinking skills and vocabulary mastery of English-speaking skills is to use survey methods using correlation and multiple regression techniques with the help of Microsoft Excel and SPSS version 20.0. After the authors analyzed the research variables critical thinking skills and vocabulary mastery of English speaking skills, it can be concluded that: (1) There is a significant influence of critical thinking skills and vocabulary mastery together on English speaking skills of the students in Serang District as evidenced with the acquisition of Sig. = 0,000 <0.05 and Fcount = 40.830 together the variables of critical thinking skills and vocabulary mastery contributed 58.9% to the variable of English speaking skills of private MA students in Serang District. (2) There is a significant influence of critical thinking ability on English speaking skills of the students in Serang District as evidenced by the acquisition of Sig. = 0,000 <0.05 and tcount = 3.807 (3) There is a significant influence of the mastery of vocabulary on English speaking skills of these students in Serang District as evidenced by the acquisition of Sig. = 0,000 <0.05 and tcount = 4,870.Key Words: critical thinking; vocabulary mastery; speaking skills